2022
DOI: 10.1002/lary.30216
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics in Otolaryngology: A Systematic Review and Meta‐analysis

Abstract: Objectives To determine the proportion of otolaryngologists with work‐related musculoskeletal discomfort (WRMD) and to review objective ergonomic data that contribute to WRMD. Study Design Systematic review and meta‐analysis. Methods A comprehensive search of the literature identified 1121 articles for initial review of which 19 (3563 participants) met criteria for qualitative discussion and eight (2192 participants) met criteria for meta‐analysis. Random effects meta‐analyses were used to estimate the proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 49 publications
(265 reference statements)
2
21
0
Order By: Relevance
“…This study demonstrated that 37% of intraoperative observations had a high ergonomic risk, while 16% had a very high risk (2). Furthermore, a recent systematic review and meta-analysis demonstrated the prevalence of workrelated MSK discomfort to be approximately 79% among practicing otolaryngologists (5). Thus, given the high prevalence of work-related musculoskeletal discomfort and the unacceptable level of ergonomic risk for common procedures, analyzing the ergonomic risk of alternative techniques and new technologies is needed to reduce and lower the risk of musculoskeletal injury for otolaryngologists.…”
mentioning
confidence: 68%
“…This study demonstrated that 37% of intraoperative observations had a high ergonomic risk, while 16% had a very high risk (2). Furthermore, a recent systematic review and meta-analysis demonstrated the prevalence of workrelated MSK discomfort to be approximately 79% among practicing otolaryngologists (5). Thus, given the high prevalence of work-related musculoskeletal discomfort and the unacceptable level of ergonomic risk for common procedures, analyzing the ergonomic risk of alternative techniques and new technologies is needed to reduce and lower the risk of musculoskeletal injury for otolaryngologists.…”
mentioning
confidence: 68%
“…Among practicing otolaryngologists, 79% reported workrelated musculoskeletal discomfort, with more than half requiring medical treatment and 16% requiring time off work. 2 Despite the breadth of the field, nearly all subspecialties of otolaryngology are affected. Prolonged static at-risk posture has been observed in head and neck surgeons while operating.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence among surgeons of WMSDs involving the neck, shoulder, and back region has been reported to be as high as 49% to 60% . Furthermore, WMSD may be associated with stiffness, fatigue, or numbness, affecting patient safety and outcomes …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations